The dependence of galaxy clustering on stellar mass, star-formation rate and redshift at z = 0.8–2.2, with HiZELS. Issue 3 (5th January 2018) - Cochrane, R K; Best, P N; Sobral, D; Smail, I; Geach, J E; Stott, J P; Wake, D A
Abstract: The deep, near-infrared narrow-band survey HiZELS has yielded robust samples of H α-emitting star-forming galaxies within narrow redshift slices at z = 0.8, 1.47 and 2.23. In this paper, we distinguish the stellar mass and star-formation rate (SFR) dependence of the clustering of these galaxies. At high stellar masses ( M * /M⊙ ≳ 2 × 10 10 ), where HiZELS selects galaxies close to the so-called star-forming main sequence, the clustering strength is observed to increase strongly with stellar mass (in line with the results of previous studies of mass-selected galaxy samples) and also with SFR. These two dependencies are shown to hold independently. At lower stellar masses, however, where HiZELS probes high specific SFR galaxies, there is little or no dependence of the clustering strength on stellar mass, but the dependence on SFR remains: high-SFR low-mass galaxies are found in more massive dark matter haloes than their lower SFR counterparts. We argue that this is due to environmentally driven star formation in these systems. We apply the same selection criteria to the EAGLE cosmological hydrodynamical simulations. We find that, in EAGLE, the high-SFR low-mass galaxies are central galaxies in more massive dark matter haloes, in which the high SFRs are driven by a (halo-driven) increased gas content.